Inhibition of poly(ADP-ribose) polymerase-1 enhances temozolomide and topotecan activity against childhood neuroblastoma - Daniel, Rachel A; Rozanska, Agata L; Thomas, Huw D; Mulligan, Evan A; Drew, Yvette; Castelbuono, Deborah J; Hostomsky, Zdenek; Plummer, E Ruth; Boddy, Alan V; Tweddle, Deborah A; Curtin, Nicola J; Clifford, Steven C (Clinical cancer research, 2009)
High-risk neuroblastoma is characterized by poor survival rates, and the development of improved therapeutic approaches is a priority. Temozolomide and topotecan show promising clinical activity against neuroblastoma. Poly(ADP-ribose) polymerase-1 (PARP-1) promotes DNA repair and cell survival following genotoxic insult; we postulated that its inhibition may enhance the efficacy of these DNA-damaging drugs in pediatric cancers. We evaluated the chemosensitizing properties of the PARP inhibitor AG014699 (Pfizer, Inc.) in combination with temozolomide and topotecan, against human neuroblastoma cells and xenografts, alongside associated pharmacologic and toxicologic indices. Addition of PARP-inhibitory concentrations of AG014699 significantly potentiated growth inhibition by both topotecan (1.5- to 2.3-fold) and temozolomide (3- to 10-fold) in vitro, with equivalent effects confirmed in clonogenic assays. In two independent in vivo models (NB1691 and SHSY5Y xenografts), temozolomide caused a xenograft growth delay, which was enhanced by co-administration of AG014699, and resulted in complete and sustained tumor regression in the majority (6 of 10; 60%) of cases. Evidence of enhanced growth delay by topotecan/AG014699 co-administration was observed in NB1691 xenografts. AG014699 metabolites distributed rapidly into the plasma (Cmax, 1.2-1.9 nmol/L at 30 min) and accumulated in xenograft tissues (Cmax, 1-2 micromol/L at 120 min), associated with a sustained suppression of PARP-1 enzyme activity. Doses of AG014699 required for potentiation were not toxic per se. These data show enhancement of temozolomide and topotecan efficacy by PARP inhibition in neuroblastoma. Coupled with the acceptable pharmacokinetic, pharmacodynamic, and toxicity profiles of AG014699, our findings provide strong rationale for investigation of PARP inhibitors in pediatric early clinical studies.